Comparison of Quality Parameters in Hen’s Eggs According to Egg Shell Color - Soria, M.A.; Bueno , D.J.; Bernigaud, I.I.C. (International Journal of Poultry Science, 2013)
The aim of this study was to evaluate some quality parameters of commercial hen’s eggs according to egg shell color. A total of 5,424 eggs were purchased from 113 supermarkets situated in 14 cities from the east-center of Entre Rios, Argentina; 3,475 were white eggshell and 1,949 eggs were brown eggshell. The values of Egg Weight (EW), Eggshell Weight (ESW), Eggshell Thickness (EST), % eggshell (% ES) and Total Shell Surface Area (TSSA) were greater in brown eggs than in white eggs. There was a significant positive correlation between EW and ESW and EW and TSSA, but EW had negative correlations with % ES. There were no significant differences in yolk (Y) and albumen (Al) pH between brown eggs and white eggs. The range of Yolk Color (YC) was 2-11 for white eggs and 2-14 for brown eggs. However, in general, eggs had similar YC in a package. This is the first report about the quality of commercial hen’s eggs from supermarkets in Argentina. Although eggs can belong to different hen’s breeding systems and ages, there are some differences in the quality parameters studied between white and brown eggs.